A comparison of future realizations of the kilogram. (24th January 2018) - Stock, M; Barat, P; Pinot, P; Beaudoux, F; Espel, P; Piquemal, F; Thomas, M; Ziane, D; Abbott, P; Haddad, D; Kubarych, Z; Pratt, J R; et al.
Abstract: The definition of the kilogram in the International System of Units (SI) is expected to be revised in 2018. The present definition of the kilogram, the mass of the International Prototype of the Kilogram (IPK), adopted in 1889, would then be replaced by a definition based on a fixed numerical value of the Planck constant. The Consultative Committee for Mass and Related Quantities has requested that, as one of the essential steps before the redefinition, a comparison of kilogram realizations based on future realization methods, Kibble9 balances and x-ray crystal density (XRCD) experiments, be organized. This comparison was carried out during 2016 in the form of a 'Pilot Study'. One aim of the study was to determine the uniformity of mass dissemination after the redefinition by comparing mass calibrations based on different future realization experiments. Another aim was to test the continuity of the mass unit across the redefinition by comparing mass calibrations based on Kibble balances and XRCD experiments with those based on the IPK. This paper describes the organization of the comparison and presents its results.